step by step explanation
Attachments:
![](https://hi-static.z-dn.net/files/d80/cfa84637b321701d93749a7765fc6d2b.jpg)
Answers
Answered by
1
Answer:
Please mark it as a Brainliest answer
Thank you :-)
Attachments:
![](https://hi-static.z-dn.net/files/d09/72109c0433f149a4352688503abbc6b3.jpg)
![](https://hi-static.z-dn.net/files/d57/01f5188629a6078fead35b7505d1404b.jpg)
Answered by
1
Ans:- (3+√2)/(3-√2) = m + n√2
= (3+√2)/(3-√2)×(3+√2)/(3+√2) = m + n√2
= (9+2+6√2)/(9-2) = m + n√2
= 11/7 + 6√2/7 = m + n√2
= m = 11/7 and n = 6/7
here is your answer
hope it will help you
Similar questions